Impact of Self-Esteem, Emotional Intelligence, and Social Anxiety on Social Relationships - Rehman, Shafaqat; Malik, Rukhsana (Kashmir Journal of Academic Research and Development, 2026)
One of the maximum simple elements of mental wellbeing and first-rate of lifestyles is the social relationships. The contemporary paper specializes in how shallowness, emotional intelligence (EI), and social tension have interaction in affecting the excellent and amount of social relationships of younger adults. The quantitative cross-sectional studies layout became used to acquire gathered records on a pattern of 320 college students (M age = 21.four years, SD = 2.31) and it became measured by using confirmed psychometric tools: the Rosenberg Self-Esteem Scale (RSES), the Wong and Law Emotional Intelligence Scale (WLEIS), the Social Interaction Anxiety Scale (SIAS), and the Network of Relationships Inventory (NRI). The SPSS v.26 and Hayes' PROCESS macro have been used to do more than one regression evaluation, Pearson correlation, and mediation evaluation. The effects confirmed that shallowness (beta =.41, p=.001) and emotional intelligence ( beta=.36, p=.001) had been crucial effective predictors of courting nice, with social tension ( beta= -.49, p=.001) being an vital bad one. The mediation evaluation confirmed that social tension partly mediated the correlation among shallowness and the exceptional of social relationships (oblique impact = -.18, 95% CI [-.27, -.09]). The powerful impact of social tension on dating delight turned into mediated through emotional intelligence. These consequences spotlight the decisive significance of intrapersonal mental variables in figuring out interpersonal outcomes and imply that interventions that concentrate on shallowness improvement, improvement of emotional skills, and reducing social tension may want to have a tremendous effect at the social lifestyles of younger adults. There are implications to counselors, educators and intellectual fitness practitioners.
Keywords: social relationships; dating nice; shallowness; emotional intelligence; social tension; mediation; younger adults